REKAYASA SISTEM INFORMASI MANAJEMEN PANTI ASUHAN MUHAMMADIYAH SUMBAWA BERBASIS WEB - Nawassyarif Nawassyarif; Nora Dery Sofya; Siti Kalkausar Djafar HS; Eri Sasmita Susanto (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Muhammadiyah Orphanage is a social welfare institution that shapes the growth and development of children who do not have families or who do not live with their families. The data management system currently running at the Muhammadiyah Orphanage is still manual which is recorded in a ledger and microsoft office word. Data processing like this will certainly make it difficult for administrators to present reports because it takes a relatively long time so as to allow errors in data management. In addition, there is no complete information about the Muhammadiyah orphanage so that donors must come to the orphanage to get information. The purpose of this thesis research is the Web-Based Engineering Information System of Muhammadiyah Sumbawa Orphanage Management. This system successfully designed and built using programming language PHP, HTML, CSS, MySQL Database, Sublime-Text Text Editor, qualitative research methods and using the Waterfall software development method. The final result of this thesis is Muhammadiyah Orphanage Management Information System Sumbawa Web-Based that will make it easier for administrators to manage orphanage data and make it easier for donors to find information about Muhammadiyah orphanages.